EVALUATE THE DIFFICULTY OF EXTRACTION OF LOWER WISDOM TEETH AT THAI BINH MEDICAL UNIVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2021)
Objective: Evaluate the difficulty of extraction of lower wisdom teeth according to Parant at ThaiBinh Medical University Hospital.Subjects and methods: Descriptive study through cross-sectional investigation of 143 subjects withlower wisdom teeth surgery at Thai Binh Medical University Hospital from November 2019 to June2020.Results: The percentage of missing wisdom teeth was about 57.34%; stuck (position A2) for 47.55%;Far/horizontal deviation accounted for 37.06%, proximal deviation accounted for 33.57%, there wasno case of inverted lower wisdom teeth; The morphology of lower wisdom teeth has 1 foot or manylegs bunched for 41.96%; density of lower jaw bone is mainly type II (normal) for 86.01%; ligamentlight around the teeth at normal level accounted for the most with 93.71%.Conclusions: The level of difficulty in extraction of lower wisdom teeth has an average score of11.83 ± 2.09.
Keywords: Lower wisdom teeth; wisdom tooth extraction; Thai Binh medical university hospital